2021
DOI: 10.3389/fcell.2021.710729
|View full text |Cite
|
Sign up to set email alerts
|

Uncharged Components of Single-Stranded DNA Modulate Liquid–Liquid Phase Separation With Cationic Linker Histone H1

Abstract: Liquid–liquid phase separation (LLPS) of proteins and DNAs has been recognized as a fundamental mechanism for the formation of intracellular biomolecular condensates. Here, we show the role of the constituent DNA components, i.e., the phosphate groups, deoxyribose sugars, and nucleobases, in LLPS with a polycationic peptide, linker histone H1, a known key regulator of chromatin condensation. A comparison of the phase behavior of mixtures of H1 and single-stranded DNA-based oligomers in which one or more of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…S2a for representative peptides: K7Y3 with aromatic side chains, K7S3 with hydrophilic side chains, and K7L3 with aliphatic side chains). Considering previous reports, 6,21,22,30,31 this behaviour confirmed that the observed condensates were not solid aggregates but liquid droplets with highly fluidic properties. To further investigate the liquid properties of the droplets, we carried out fluorescence recovery after photobleaching (FRAP) experiments, a method commonly used to measure the mobility of molecules inside droplets.…”
Section: Design Of a Model Llps Systemsupporting
confidence: 87%
See 2 more Smart Citations
“…S2a for representative peptides: K7Y3 with aromatic side chains, K7S3 with hydrophilic side chains, and K7L3 with aliphatic side chains). Considering previous reports, 6,21,22,30,31 this behaviour confirmed that the observed condensates were not solid aggregates but liquid droplets with highly fluidic properties. To further investigate the liquid properties of the droplets, we carried out fluorescence recovery after photobleaching (FRAP) experiments, a method commonly used to measure the mobility of molecules inside droplets.…”
Section: Design Of a Model Llps Systemsupporting
confidence: 87%
“…π-π Interactions between the side chain of aromatic amino acids and nucleobases contribute to the formation of droplets between proteins and nucleic acids. 21,22,40 The nucleobases are embedded in the dsDNA of dR15 and its complementary strand (dsDNA15) due to base pairing, thus preventing access of the peptides to the nucleobases. Therefore, we assumed that dsDNA15 could be used to examine the effect of the nucleobases.…”
Section: Generality and Mechanism Of The Effects Of Non-ionic Amino A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Phase behavior also differs between single-stranded and double-stranded sequences. High LLPS potential of unfolded single-stranded nucleic acids with exposed nucleobases is increased by contributing π-electron–related interactions ( 54 ). These include π–π and cation–π interactions of the nucleobase components ( 54 ) and sugar–π contacts enabled by deoxyribose moieties ( 55 ).…”
Section: Rna In Biomolecular Condensatesmentioning
confidence: 99%
“…High LLPS potential of unfolded single-stranded nucleic acids with exposed nucleobases is increased by contributing π-electron–related interactions ( 54 ). These include π–π and cation–π interactions of the nucleobase components ( 54 ) and sugar–π contacts enabled by deoxyribose moieties ( 55 ). In contrast, double-stranded DNA has higher charge density than single-stranded DNA, and binds more strongly to polycations, thereby forming solid aggregates (at low ionic strength) or a liquid–crystalline phase (at high ionic strength), while remaining base-paired ( 53 ).…”
Section: Rna In Biomolecular Condensatesmentioning
confidence: 99%